Dignity Without Dance - Dr Kiese Kituevewa, Historian, Descendant of Bana Nkole (NY, USA); Dr Lawren Mutamba, Psychologist (GA, USA); Dr Clark K Nzundu, Historian, (GA, USA) (My University, 2025)
This paper argues that the Kimbanguist prohibition on dancing is not merely a moral “puritan” rule, but, within a specific Kongo–Kimbangu memory stream, a disciplined memorial technology forged under colonial humiliation and resistance. It then explains how a rule can remain formally intact while its civilizational meaning collapses locally. We propose a two-track model: scripturalization (Bible-centered legitimacy becoming compulsory as a preaching template) and westernization (prestige incentives that stigmatize ancestral memory as “obsolete,” “merely cultural,” or “demonic”). Using “no dance” as a case study, the paper introduces a falsifiable drift-measurement protocol grounded in two primary corpora: (i) public leadership statements since 2005 (video corpus) and (ii) a documented internal governance device, weekly Tuesday reminders instructing preachers to “restore the church as it was” and teach Kimbangu’s civilizational inheritance “as it is.” The existence of repeated re-anchoring directives alongside persistent divergence supports an implementation gap + prestige drift interpretation rather than a claim that “the institution changed the rules.” The ecumenical interface is treated as an amplifier: Kimbanguist entry into the World Council of Churches (WCC) in 1969 created long-term incentives for doctrinal legibility, while the WCC’s 2021 discontinuation of membership confirms that legibility pressures were structurally real.
Colonial Humiliation, Ritual Memory, and Meaning-Drift in Kimbanguism After Ecumenical Integration (1921–2025)